Reinforcement of traditional timber frame walls - Poletti, Elisa (2021)
Timber frame walls are common structural elements adopted in many countries for different purposes. They constitute an important cultural heritage of different parts of the world and the necessity often arises to intervene in such structures for their preservation. Different strengthening techniques have been adopted when retrofitting timber frame walls, some traditional and others more innovative. As the response of the walls, particularly to horizontal actions, is governed by their connections, retrofitting is usually concentrated at the joints, but interventions can also be carried out on timber members or on infill. In this chapter, an overview of possible retrofitting techniques is presented, focusing on their advantages and disadvantages and their effects on the overall behaviour of the wall. The presented solutions focus mainly on experimental and in situ interventions performed for seismic purposes.